Homogeneity and Possible Replacement of Populations of the Dengue Vectors Aedes aegypti and Aedes albopictus in Indonesia - Garjito, Triwibowo Ambar; Widiarti, Widiarti; Hidajat, Muhammad Choirul; Handayani, Sri Wahyuni; Mujiyono, Mujiyono; Prihatin, Mega Tyas; Ubaidillah, Rosichon; Sudomo, Mohammad; Satoto, Tri Baskoro Tunggul; Manguin, Sylvie; Gavotte, Laurent; Frutos, Roger (Frontiers in Cellular and Infection Microbiology, 2021)
Currently, Aedes aegypti, the principal vector of dengue virus in Indonesia, has spread throughout the archipelago. Aedes albopictus is also present. Invasion and high adaptability of the Aedes mosquitoes to all of these areas are closely related to their ecology and biology. Between June 2016 and July 2017, larval and adult mosquito collections were conducted in 43 locations in 25 provinces of Indonesia using standardized sampling methods for dengue vector surveillance. The samples collected were analyzed for polymorphism and phylogenetic relationship using the mitochondrial cox1 gene and the nuclear ribosomal internal transcribed spacer 2 (ITS2). Almost all Ae. aegypti samples collected in this study (89%) belonged to the same haplotype. A similar situation is observed with the nuclear ITS2 marker. Populations of Ae. aegypti characterized few years ago were genetically different. A closely related observation was made with Aedes albopictus for which the current populations are different from those described earlier. Ae. aegypti populations were found to be highly homogenous all over Indonesia with all samples belonging to the same maternal lineage. Although difficult to demonstrate formally, there is a possibility of population replacement. Although to a lower extent, a similar conclusion was reached with Ae. albopictus.